Alkylthienyl substituted asymmetric 2D BDT and DTBT-based polymer solar cells with a power conversion efficiency of 9.2%. Issue 5 (19th January 2018) - Gu, Chuantao; Liu, Deyu; Wang, Junyi; Niu, Qingfen; Gu, Chunyang; Shahid, Bilal; Yu, Bing; Cong, Hailin; Yang, Renqiang
Abstract : An alkyl thiophene unit was employed for the first time as a side chain substituent on an asymmetric benzodithiophene (BDT) building block in the design of novel light-harvesting polymers. Abstract : An alkyl thiophene unit was employed for the first time as a side chain substituent on an asymmetric benzodithiophene (BDT) building block in the design of novel light-harvesting polymers. A new D–A type polymer (PBDTTh –DTff BT) based on alkylthienyl asymmetric BDT and the well-known 4, 7-di(thiophen-2-ethylhexyl)-5, 6-difluoro-2, 1, 3-benzothiadiazole (DTff BT) was synthesized through a palladium catalyzed Stille coupling reaction. Efficient bulk heterojunction solar cells were fabricated by blending PBDTTh –DTff BT with PC71 BM. The optimized PBDTTh –DTff BT-based photovoltaic device exhibits an open circuit voltage ( V OC ) of 0.87 V, a short-circuit current density ( J SC ) of 15.06 mA cm −2, a fill factor (FF) of 70.4% and a high power conversion efficiency (PCE) of 9.22%. The PCE was higher than the polymers which have the same backbone structure but also have the 1D or 2D symmetric BDT unit. In addition, a PCE of 7.83% with a V OC of 0.91 V, a J SC of 13.62 mA cm −2, and an FF of 63.2% was obtained for PBDTTh –DTff BT/ITIC, which is also impressive for non-fullerene PSCs. The results indicate that our design strategy of introducing an alkylthienyl unit as side chain to fabricate asymmetric BDT-based polymer is efficient in improving the photovoltaic performance.